2020
DOI: 10.1111/bcp.14171
|View full text |Cite
|
Sign up to set email alerts
|

Direct oral anticoagulants uptake and an oral anticoagulation paradox

Abstract: Oral anticoagulation (OAC) for stroke prevention in patients with atrial fibrillation is underutilised. One of the impediments to warfarin therapy is the frequent monitoring required, usually at a specialised warfarin clinic. The advent of direct oral anticoagulants (DOACs) facilitates OAC therapy without an onerous monitoring regimen. This benefit may result in the more significant adoption of DOACs in areas without a warfarin clinic. This study analysed national administrative data for reimbursed pharmacy cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…28 Not only have they become the first-line treatment for stroke prevention in patients with non-valvular AF, but they are also prescribed for an increasing number of additional indications. 29 In accordance with previous studies, we found that 1 in 8 of all stroke patients had been on anticoagulation therapy. However, in the subgroup of AF patients who are potentially eligible for IVT, 1 in 4 patients had prior anticoagulation treatment.…”
Section: Discussionsupporting
confidence: 92%
“…28 Not only have they become the first-line treatment for stroke prevention in patients with non-valvular AF, but they are also prescribed for an increasing number of additional indications. 29 In accordance with previous studies, we found that 1 in 8 of all stroke patients had been on anticoagulation therapy. However, in the subgroup of AF patients who are potentially eligible for IVT, 1 in 4 patients had prior anticoagulation treatment.…”
Section: Discussionsupporting
confidence: 92%
“… Funding: national funding body COI: none Keating et al (2020), USA [ 52 ] To understand adoption of bevacizumab by oncologists for patients with cancer using network analysis method Quantitative Insurance claim database Secondary care bevacizumab 44,012 patients, 3261physicians, 51 hospital referral regions Patient’s clinical and demographic characteristics; Age of prescriber; Peer influence. Funding: national funding body COI: one author received consultant fees from Grail Kennedy et al (2020), Ireland [ 53 ] To compare the use of direct oral anticoagulants in areas with warfarin clinics compared to those without Quantitative Pharmacy claims database shapefiles of warfarin clinics and areas Primary care apixaban, dabigatran, edoxaban, rivaroxaban Presence or absence of hospital-based warfarin clinics- no effect. Funding: national funding body COI: none Kereszturi et al (2015), Hungary [ 54 ] To identify socio-demographic, workplace, practice, prescribing and patient characteristics of the early prescribers of the newly marketed innovative medicines Quantitative DoktorInfo prescription database Secondary care vildagliptin with metformin and metformin with sitagliptin combinations 318 physicians Portfolio width and prescribing volume of prescriber; Number of patients looked after by prescriber and number of consultations per patient; Prescribing of other branded medicines; Proportion of patients treated with insulin.…”
Section: Resultsmentioning
confidence: 99%
“…Medium to high quality studies suggested younger [ 33 , 48 , 53 , 62 ] or older [ 27 , 42 ], male [ 23 , 42 , 48 , 85 ], graduating from a top-20 medical [ 23 , 62 ] or foreign medical school [ 48 ] prescribers were earlier adopters. Other medium to high quality studies reported that age [ 29 , 42 , 48 ], gender [ 29 , 62 ], prescribers’ length of practice [ 35 , 85 ], graduating from a top-20 medical school [ 48 , 62 ] did not influence prescribing decisions.…”
Section: Resultsmentioning
confidence: 99%
“…previously and is accompanied by a large increase in expenditure due to the cost of reimbursing DOAC prescriptions. 11 Warfarin has been the gold standard for prevention of stroke in high-risk patients with AF, but it has numerous disadvantages leading to considerable F I G U R E 5 Ischaemic stroke patients with previously diagnosed atrial fibrillation and their antithrombotic treatment at the time of admission in the National Stroke Register dataset F I G U R E 6 Ischaemic stroke patients with previously diagnosed atrial fibrillation prescribed an oral anticoagulant prior to admission in the National Stroke Register dataset underutilisation. 19 Its narrow therapeutic window along with its numerous drug and food interactions make it less appealing and problematic to manage.…”
Section: The Large Increase In Oac Utilisation In Ireland Has Been Reportedmentioning
confidence: 99%